Leptin acts as a growth factor for colorectal tumours at stages subsequent to tumour initiation in murine colon carcinogenesis. Issue 10 (15th March 2011) - Endo, Hiroki; Hosono, Kunihiro; Uchiyama, Takashi; Sakai, Eiji; Sugiyama, Michiko; Takahashi, Hirokazu; Nakajima, Noriko; Wada, Koichiro; Takeda, Kiyoshi; Nakagama, Hitoshi; Nakajima, Atsushi
Abstract : Background and aims: Obesity increases the risk of colorectal cancer (CRC). Serum leptin levels are markedly elevated in obese individuals, but the involvement of leptin in CRC growth remains unclear. We explored the hypothesis that leptin signalling regulates the growth of CRC, by examining the effects of leptin deficiency on murine colon tumour growth. Methods: We used genetic (leptin-deficient and leptin receptor-deficient) models of obesity and investigated carcinogen-induced colon polyp formation and cell proliferation in the colonic epithelium. Colonic tissues and cell lines were analysed by histopathology and molecular-biology methods. Results: A significant increase in the proliferative activity of normal colonic epithelial cells was observed in the obesity model; on the other hand, significant decrease of tumour cell proliferation was observed in leptin-deficient tumours, and tumour growth was dramatically inhibited in leptin-deficient and leptin-receptor-deficient mice despite the animals exhibiting severe obesity. Notably, a marked increase of the leptin receptor (ObR) expression levels was observed in colon tumours as compared to the normal epithelium. Nuclear β-catenin staining was pronounced in all tumours, irrespective of leptin deficiency, whereas altered cellular localisation of β-catenin was not observed in the normal colonic epithelial cells. In vitro, β-catenin knockdown decreased ObR expression, and stimulation of recombinant Wnt increased ObR expression. In addition, the proliferative and survival effects of leptin were found to be mediated by the ObR/signal transducer and activator of transcription 3 (STAT3) signalling in colon tumours. Conclusions: Our findings indicate that leptin is important for CRC growth in obesity, and acts as a growth factor for CRC at stages subsequent to tumour initiation in colorectal carcinogenesis. Thus, inhibition of leptin signalling may be an effective strategy for therapy and prevention of colonic adenoma and cancer, which show activation of Wnt signalling.